Diversity & inclusion in early childhood : an introduction - Devarakonda, Chandrika; Sage eBooks (London : SAGE, 2016)
Covering a wide range of concepts and taking a broader perspective of what inclusion entails, this book offers an overview of current research, policy and practice in diversity and inclusion in the early years. It is a clear introduction to what inclusive practice means for those working with young children in the early stages of their lives.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 20, 2016).
Keywords: Early childhood education; Multicultural education; Electronic books